2019
DOI: 10.1161/atvbaha.119.312765
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Vascular Smooth Muscle Cells by Histone H3 Lysine 9 Dimethylation Attenuates Target Gene-Induction by Inflammatory Signaling

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Except for regulating autophagy, EHMT2 was recently reported to regulating inflammatory VSMC phenotype by dimethylating H3K9 (H3K9me2). H3K9me2 was enriched at a subset of inflammation-responsive gene promoters, including MMP3, MMP9, MMP12, and IL6, in VSMCs to affect post-injury neointima formation and atherosclerotic lesions [44]. These studies indicated that EHMT2 may be involved in aortic dissection, aortic aneurysm and atherosclerosis via regulating autophagy or inflammatory response, but the exact roles and mechanisms of EHMT2 in these vasculopathy need further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Except for regulating autophagy, EHMT2 was recently reported to regulating inflammatory VSMC phenotype by dimethylating H3K9 (H3K9me2). H3K9me2 was enriched at a subset of inflammation-responsive gene promoters, including MMP3, MMP9, MMP12, and IL6, in VSMCs to affect post-injury neointima formation and atherosclerotic lesions [44]. These studies indicated that EHMT2 may be involved in aortic dissection, aortic aneurysm and atherosclerosis via regulating autophagy or inflammatory response, but the exact roles and mechanisms of EHMT2 in these vasculopathy need further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Our study identifies additional phases of activation where VSMCs that could be subject to regulation, including VSMC priming, cell cycle activation, VSMC loss and migration across the intimal layer. Understanding how documented regulators of VSMC function in disease 1,36,41 and novel pathways - such as retinoic acid signaling and efferocytosis identified by scRNA-seq analysis of atherosclerotic plaque cells 16,33 -impact on these mechanisms will provide important insight into how targeting of vessel wall cells could be achieved to limit cell accumulation and disease severity. The existence of cells in human arteries that correspond to the murine SCA1+ VSMCs and the genetic evidence linking variable expression to cardiovascular disease highlight this cell population a promising starting point.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that histone H3K9me2 in patients with hyperthyroidism is lower than it is in a normal control group, while the expression of the JHDM2A gene is significantly higher than it is in a normal control group (Yan et al, 2019). It has been observed that the decrease in H3K9me2 in vascular smooth muscle cells is accompanied by an increase in inflammation, and there is a high level of H3K9me2 in the promoter region of arteriosclerosis genes associated with cardiovascular disease (Harman et al, 2019). In addition, there is evidence that histone modification plays an important role in regulating the expression of DNA damage repair‐related factors (Mao & Wyrick, 2016).…”
Section: Discussionmentioning
confidence: 99%